Efficacy of a cognitive intervention program in patients with mild cognitive impairment - Rojas, Galeno J. (2012)
Background: Mild cognitive impairment (MCI) is a transitional state between normal aging and dementia. Identifying this condition would allow early interventions that may reduce the rate of progression to Alzheimer's disease (AD). We examined the efficacy of a six-month cognitive intervention program (CIP) in patients with MCI and to assess patients' condition at one-year follow-up. Methods: Forty-six MCI participants assessed with neuropsychological, neurological, neuropsychiatry, and functional procedures were included in this study and followed up during a year. The sample was randomized into two subgroups: 24 participants (the trained group) underwent the CIP during six months while 22 (control group) received no treatment. Sixteen participants dropped out of the study. The intervention focused on teaching cognitive strategies, cognitive training, and use of external aids, in sessions of two hours, twice per week for six months. Cognitive and functional measures were used as primary outcome and all were followed up at one year. Results: The intervention effect (mean change from baseline) was significant (p < 0.05) on the Mini-Mental State Examination (1.74), the Clinical Dementia Rating Scale (0.14), the Boston Naming Test (2.92), block design (-13.66), matrix reasoning (-3.07), and semantic fluency (-3.071) tasks. Four patients (one trained and three controls) progressed to dementia after one year of follow-up. Conclusions: These results suggest that persons with MCI can improve their performance on cognitive and functional measures when provided with early cognitive training and it could persist in a long-term follow-up.